Psychometric properties of a theory of planned behavior questionnaire for assessing the midwives’ intention to provide planned home birth services in Nigeria - Muhammed, Auwalu; Shariff Ghazali, Sazlina; Md Said, Salmiah; Hassan, Mairo; Lee, Khuan (Taylor and Francis Group, 2020)
We developed and psychometrically tested a Theory of Planned Behavior (TPB) questionnaire which focused on assessing the midwives’ intention to provide planned home birth (PHB) services. This is a quantitative, cross-sectional survey, conducted among 226 midwives working in ten participating health facilities. The reliability and validity of the theoretical constructs were assessed. The Cronbach’s alpha values were >0.8 for all scales, suggesting satisfactory internal consistency. Confirmatory factor analysis revealed sufficient convergent validity (the average variance extracted was >0.5 for each construct) and discriminant validity. The study gathered an evidence of the usefulness of TPB in the specific context of PHB.